Imperatorin attenuates cardiac remodelling and dysfunction in high-fat/high-fructose diet-fed rats by modulating oxidative stress, inflammation, and Nrf-2 expression. (April 2022) - Prasartthong, Patoomporn; Pakdeechote, Poungrat; Maneesai, Putcharawipa; Meephat, Sariya; Rattanakanokchai, Siwayu; Wunpathe, Chutamas; Apaijit, Kwanjit; Bunbupha, Sarawoot
Highlights: Impertorin alleviated high-fat/high-fructose diet-induced insulin resistance, dyslipidemia, and hypertension. Impertorin alleviated high-fat/high-fructose diet-induced LV remodeling and dysfunction. Impertorin exhibited antioxidant property by modulation the expression of MDA level and CAT activity. Impertorin exhibited anti-inflammatory property by suppressing the expression of TNF-α and IL-6 levels. Impertorin enhanced protein Nrf-2 expression. Abstract: Imperatorin, an active natural furocoumarin, exerts a wide range of biological activities. In the present study, the therapeutic effects of imperatorin on cardiac function and remodelling and the possible underlying mechanisms involved in high-fat/high-fructose diet (HFFD)-fed rats were investigated. Male Sprague–Dawley rats were fed a high-fat diet plus 15 % fructose in drinking water for 16 weeks. HFFD-fed rats were treated with imperatorin (15 or 30 mg/kg/day) for the last 4 weeks. Treatment of HFFD-fed rats with imperatorin significantly reduced dyslipidaemia, hyperinsulinaemia, and hypertension. Imperatorin markedly alleviated HFFD-induced cardiac morphology alterations and left ventricular (LV) dysfunction. Imperatorin also significantly decreased malondialdehyde concentration and increased catalase activity in plasma and cardiac tissue. Additionally, decreased plasma tumour necrosis factor-α and interleukin-6 concentrations, together with restoration of cardiac nuclear factor-erythroid 2-related factor 2 (Nrf-2) protein expression, were also observed after treatment with imperatorin. These findings indicated that imperatorin alleviates HFFD-induced cardiac remodelling and LV dysfunction in rats. The possible underlying mechanism may involve the reduction of oxidative stress and inflammation, and the restoration of Nrf-2 expression.